Effect of Occupational Exposure to Herbicides on Oxidative Stress in Sprayers - Unchisa Intayoung; Klintean Wunnapuk; Kanyapak Kohsuwan; Ratana Sapbamrer; Supakit Khacha-ananda (Elsevier, 2021)
Background: Herbicides such as glyphosate, paraquat, and 2,4-dichlorophenoxyacetic acid have been reported to cause adverse side effects through production of reactive oxygen species. However, there were no data representing the adverse effects of a mixture herbicide usage in farmers, especially the changes in oxidative marker and antioxidant defense. This study aimed to determine the urinary malondialdehyde (MDA) and glutathione (GSH) level in farmers using mixed herbicides. Methods: Ninety-three farmers were recruited, and two spot urine samples (before and after work) were collected. The urinary MDA level was evaluated by thiobarbituric acid reactive substance assay, and the urinary GSH level was determined using the enzymatic recycling method. Results: Sixty-two percent of the participants were men, and 59% of the participants worked in a farm for 20-40 years. The common combinations of herbicide usage were glyphosate with 2,4-dichlorophenoxyacetic acid (36.5%). There was no significant difference between pre- and post-work urinary MDA and GSH levels among the 3 groups of herbicides. However, the urinary MDA levels in farmers using the combination of glyphosate and paraquat were significantly higher than those found in farmers using glyphosate alone. The associated factors with changes in MDA levels found that the exposure intensity index (B = 0.154), the cumulative exposure intensity index (B = 0.023), and wearing gloves while working (B = −2.347) were found to be significantly associated with MDA level. Conclusion: The results suggest that the combined use of glyphosate and paraquat caused a significant increase in urinary MDA levels. Moreover, intensity of exposure to herbicide and wearing gloves were associated with the level of MDA.